Extraction of Cell‐Free Whole Blood Plasma Using a Dielectrophoresis‐Based Microfluidic Device. Issue 3 (18th July 2018) - Yang, Fang; Zhang, Ying; Cui, Xi; Fan, Yutong; Xue, Ying; Miao, Haipeng; Li, Guiying
Abstract : Blood is the most valuable and convenient source of disease diagnostic biomarkers, but plasma must be extracted from blood prior to further biomarker detection and analysis. Traditional plasma extraction methods depend greatly on benchtop equipment and are often cumbersome, time‐consuming, and unsuitable for point‐of‐care (POC) applications. On the other hand, highly diluted blood plasma extraction methods potentially introduce greater test result uncertainty and lower detection sensitivity. Because simpler integrated and more efficient plasma extraction methods that avoid sample dilution are highly desired, the authors develop a simple dielectrophoresis (DEP)‐based microfluidic device for plasma extraction from whole blood. The separation strategy is straightforward and the device is easy to manufacture, due to its lack of mechanistic complexity. Human plasma is extracted from whole blood without dilution or other complex pre‐handling steps and attained purity approaching 100%, with a calculated plasma yield of ≈31%. In addition, flow rate and voltage effects on extraction efficiency are also evaluated. This work provides a simple, integrated, non‐invasive, continuous, and efficient method for plasma extraction without dilution using a lab‐on‐chip platform with potential application for real‐time biomarker detection from blood. Abstract : Blood is the most valuable and convenient source of disease diagnostic biomarkers, but plasma must be extracted from blood prior to further biomarker detection and analysis. The authors develop a simple dielectrophoresis (DEP)‐based microfluidic device for plasma extraction from whole blood without dilution. This work provides a simple, integrated, non‐invasive, continuous, and efficient method for plasma extraction without dilution using a lab‐on‐chip platform with potential application for real‐time biomarker detection from blood.